Proses Pembelajaran Anak Usia Dini - Eny Munisah (Universitas Muhammadiyah Kotabumi, 2020)
The learning process of early childhood emphasizes the process of learning through play, to practice basic skill acquired through play activities. Through play activities children can involve themselves and explore to strengthen the things they have and find new knowledge. The learning process carried out aims to optimize aspects of child development. The learning process by playing strategies are carried out is appropriate with the goals determined goals, and the learning model through play used is guided and directed play, because it tends to use props. The learning process tends to be classical with the same material and method simultaneously and applied to all children, and the learning process has not varied according to the uniqueness of each child, so that the learning process has not conditioned the child to choose the angle of play according to their interests and choices.